2020
DOI: 10.3390/biom10101421
|View full text |Cite
|
Sign up to set email alerts
|

α-Bisabolol, a Dietary Bioactive Phytochemical Attenuates Dopaminergic Neurodegeneration through Modulation of Oxidative Stress, Neuroinflammation and Apoptosis in Rotenone-Induced Rat Model of Parkinson’s Disease

Abstract: Rotenone (ROT), a plant-derived pesticide is a well-known environmental neurotoxin associated with causation of Parkinson’s disease (PD). ROT impairs mitochondrial dysfunction being mitochondrial complex-I (MC-1) inhibitor and perturbs antioxidant-oxidant balance that contributes to the onset and development of neuroinflammation and neurodegeneration in PD. Due to the scarcity of agents to prevent the disease or to cure or halt the progression of symptoms of PD, the focus is on exploring agents from naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 69 publications
(75 reference statements)
1
20
0
1
Order By: Relevance
“…Proinflammatory cytokines, including TNF‐α, IL‐1β, and IL‐6, are found in either cerebrospinal fluid (CSF) or in affected brain regions in PD (Nagatsu et al., 2000). Rotenone‐injected animals displayed the occurrence of neuroinflammation (Javed et al., 2020). Previous studies have indicated that the survival of dopaminergic neurons could be protected via inhibiting neuroinflammatory responses (Furuyashiki, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines, including TNF‐α, IL‐1β, and IL‐6, are found in either cerebrospinal fluid (CSF) or in affected brain regions in PD (Nagatsu et al., 2000). Rotenone‐injected animals displayed the occurrence of neuroinflammation (Javed et al., 2020). Previous studies have indicated that the survival of dopaminergic neurons could be protected via inhibiting neuroinflammatory responses (Furuyashiki, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…α-Bisabolol is used in a wide range of cosmetic formulations, as a skin conditioning agent, because of its anti-inflammatory and anti-allergic properties (Madhavan, 1999). However, it is also appreciated agents from naturally occurring dietary phytochemicals with gastro protective effects, antitumor activity and many others pharmacological properties (de Siqueira et al, 2014;Javed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…α -bisabolol significantly suppressed expression of inflammatory cytokines as well as COX-2 and iNOS at both the mRNA and protein levels. Previous studies also report a similar effect mediated by α -bisabolol in suppressing COX-2 and iNOS expression in LPS-induced macrophages and in a rotenone-induced rat model of Parkinson's disease [ 14 , 41 ].…”
Section: Discussionmentioning
confidence: 65%